2007
DOI: 10.1248/bpb.30.297
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin-8S-Induced Intracellular Calcium Signaling in Acutely Isolated Periaqueductal Gray Neurons of the Rat

Abstract: The midbrain periaqueductal gray (PAG) plays a crucial role in the integration of an animal's behavioral, somatic, and autonomic responses to threat, stress, and pain. 1,2) In particular, the PAG is a major site for modulation of nociception and a part of descending antinociceptive systems that relay via the rostral ventromedial medulla (RVM) to the spinal cord. 3,4) In addition, stimulation of dorsal PAG in several species produced defense reaction, anxiety, and fear, and lesions of the PAG produced anxiolyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
2
8
1
Order By: Relevance
“…Together, these results suggest that the cholecystokinin-induced inward current is largely mediated by CCK1 receptors; however, a role for CCK2 receptors cannot be excluded. The present results differ to previous studies in the PAG where the postsynaptic effects of CCK-S were largely abolished by the CCK2 receptor antagonist L-365, 260 (10 mM), but not by 10 mM devazepide (Yang et al, 2006(Yang et al, , 2007. It might also be noted that CCK2 antagonists have been reported to block the increase in firing rate of PAG neurons, also the anxietyrelated activity, defensive rage, and the pro-nociceptive/ anti-opioid effects produced by CCK-S and pentagastrin within the PAG (Bertoglio and Zangrossi, 2005;Brack and Lovick, 2007;Chen et al, 1998;Liu et al, 1994;Luo et al, 1998;Netto and Guimaraes, 2004;Tortorici et al, 2003).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Together, these results suggest that the cholecystokinin-induced inward current is largely mediated by CCK1 receptors; however, a role for CCK2 receptors cannot be excluded. The present results differ to previous studies in the PAG where the postsynaptic effects of CCK-S were largely abolished by the CCK2 receptor antagonist L-365, 260 (10 mM), but not by 10 mM devazepide (Yang et al, 2006(Yang et al, , 2007. It might also be noted that CCK2 antagonists have been reported to block the increase in firing rate of PAG neurons, also the anxietyrelated activity, defensive rage, and the pro-nociceptive/ anti-opioid effects produced by CCK-S and pentagastrin within the PAG (Bertoglio and Zangrossi, 2005;Brack and Lovick, 2007;Chen et al, 1998;Liu et al, 1994;Luo et al, 1998;Netto and Guimaraes, 2004;Tortorici et al, 2003).…”
Section: Discussioncontrasting
confidence: 99%
“…The CCK-S-induced inward current was likely to be mediated by activation of a non-selective cation conductance and inhibition of an inwardly rectifying potassium conductance, because it was associated with a near parallel shift in the current-voltage relationship. Although this differs to a previous study, in which it was found that CCK-S exerted an effect solely by inhibiting an inwardly rectifying potassium conductance in dorsolateral PAG neurons (Yang et al, 2006(Yang et al, , 2007, it is similar to our previous findings for neurotensin and substance P (Drew et al, 2005;Mitchell et al, 2009).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…More and more evidence indicated that CCK and native or recombinant CCK1 and CCK2 receptors were coupled to the mobilization of intracellular Ca 2C (Matozaki et al 1988, Lee et al 1993, Dunlop et al 1996, Shimazoe et al 2008. The antagonist of CCK1 or CCK2 receptor could significantly affect physiological functions of different cell types by modulating intracellular Ca 2C concentration (Muller et al 1997, Simasko et al 2002, Yang et al 2007). Ca 2C is essential for the activation of the sAC/cAMP/PKA pathway in sperm.…”
Section: Discussionmentioning
confidence: 99%